2004
DOI: 10.1088/0953-4075/37/18/014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple photoionization following 3d5/2-shell threshold ionization of Xe

Abstract: Multiple photoionization of Xe near the 3d 5/2 -shell threshold photoionization region is studied by threshold electron-ion coincidence spectroscopy. The coincidence spectra of Xe 3+ to Xe 7+ ions exhibit characteristic profiles associated with multi-step post-collision interactions in Auger cascades following 3d 5/2 -shell threshold photoionization. The Auger cascade decay channels leading to the formation of multiply charged ions are deduced from the energies of the profile peaks, which increase gradually wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(41 reference statements)
4
13
0
Order By: Relevance
“…For Xe: 1s f El-Shermi et al [27]; 2s f El-Shermi et al [27]; 2p f El-Shermi al [27]; 3s and 4s k Kochur et al [38], theoretical calculation; no experimental data available; 3p l Saito and Suzuki [32]; 3d l Saito and Suzuki [32]; similar experimental values have been reported in [33]; also in agreement with differential data for 3d 5/2 initial vacancy in [29,33,34].4p m Hikosaka et al [35]; the theoretical results by Kochur et al [38] are in good agreement with these experimental values; 4d p Hayaishi et al [36] and Kämmerling et al [37]; the Xe N-shell values by Carlson et al [12] include O-shell ionization and are not presented in this table.…”
Section: Branching Ratiossupporting
confidence: 79%
See 1 more Smart Citation
“…For Xe: 1s f El-Shermi et al [27]; 2s f El-Shermi et al [27]; 2p f El-Shermi al [27]; 3s and 4s k Kochur et al [38], theoretical calculation; no experimental data available; 3p l Saito and Suzuki [32]; 3d l Saito and Suzuki [32]; similar experimental values have been reported in [33]; also in agreement with differential data for 3d 5/2 initial vacancy in [29,33,34].4p m Hikosaka et al [35]; the theoretical results by Kochur et al [38] are in good agreement with these experimental values; 4d p Hayaishi et al [36] and Kämmerling et al [37]; the Xe N-shell values by Carlson et al [12] include O-shell ionization and are not presented in this table.…”
Section: Branching Ratiossupporting
confidence: 79%
“…However, it is fair to note that the earlier measurements by Carlson and collaborators in the '60s, corrected to exclude outer-shell ionization, are in good agreement with recent ones using COLTRIMS techniques (see for example the corrected values by Krause et al [13] for Kr, which are quite close to recent values by Tamenori et al [17] and Armen et al [18]). For Kr: 1s f El-Shermi et al [27]2s f El-Shermi et al [27]; 2p g Morishita et al [28], other values can be found in Armen et al [18] and in El-Shermi et al [27]; 3s h Tamenori et al [17]; 3p h Tamenori et al [17], the values displayed are weighted mean values of 3p 3/2 and 3p 1/2 ; alternative values (differences less than 10%) can be found in Brünken et al [24], Matsui et al [29] and Armen et al [18]; 3d h Tamenori et al [17], other similar data in Brünken et al [24] and Saito et al [30], recent theoretical values by Zeng et al [31] are in good agreement too; 4s, 4p h Tamenori et al [17] show that the energy threshold of Kr 2+ is above Kr + (4s −1 ), so the decay from Kr + (4s −1 ) to Kr 2+ is not energetically possible .…”
Section: Branching Ratiosmentioning
confidence: 92%
“…The most prominent features of the xenon photoionization cross sections in this energy range are due to inner shell ionization of a 3d electron. In the past, inner-shell 3d-photoabsorption and 3d-photoionization of neutral xenon atoms has been extensively studied both experimentally [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and theoretically [24][25][26][27][28][29][30][31][32][33][34][35]. To the best of our knowledge there are no such studies for xenon ions, except for the theoretical work of Tong et al [31] on 3d → εf partial ionization of Xe + and Xe 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…These processes were extensively studied by Carlson, Krause and co-workers [33][34][35][36][37][38] in photoionization. The advent of new experimental techniques in photon-atom research in the last two decades has contributed to a detailed knowledge of the Auger-type processes, the intermediate steps and cascades [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%